(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the results of research on improving the technical training of 11-13-year-old breaststroke swimmers. Directions for improving breaststroke swimming technique of young swimmers and recommendations for implementation are covered in detail. In addition, information related to the study of the relationship between technical training and other types of training is presented.